Experimental assessment of stamping parameters in a non-isothermal sheet metal forming technology - Nur Asyran Wanie , Baharom (2013)
Hot stamping with high strength steel is becoming more popular in automotive industry. The hot stamping technology (press hardening) is one of the most successful in producing complex components with superior mechanical properties. The hot stamping process can be described by the following steps; punching of dog bone specimen, heating to 950◦C in a furnace to austenitization followed by simultaneous forming and quenching in forming tools. In hot stamping, specimen is hot formed and press hardened in a water-cooled tool to achieve high strength. Hence, design of the tool with necessary cooling significantly influences the final properties of the specimen and the process time. This research was carried out to analyze of flow rate and stamping time while stamping process for boron steel 22MnB5 in order to achieve the cooling rate and tensile strength of the material. In this paper a new method based on systematic optimization to design cooling ducts in tool is introduced. Three different location of cooling system were used in this experiment which is cooling system at punch only, cooling system at die only and cooling system at both of punch and die simultaneously. Results show that, different type of flow rate parameters and location of cooling system has significant effect to cooling rate and ultimate tensile strength.